Enterococcus faecalis OG1RF induces apoptosis in MG63 cells via caspase‐3/‐8/‐9 without activation of caspase‐1/GSDMD. (13th August 2021) - Li, Yang; Wen, Cheng; Zhong, Jialin; Ling, Junqi; Jiang, Qianzhou
Abstract: Objective: Regulated cell death is key in the pathogenesis of persistent apical periodontitis. Here, we investigated the mechanisms of regulated cell death in osteoblast‐like MG63 cells infected with Enterococcus faecalis OG1RF. Materials and methods: MG63 cells were infected with live E. faecalis OG1RF at the indicated multiplicity of infection for the indicated infection time. We evaluated the cells by flow cytometry, terminal deoxynucleotidyl transferase dUTP nick end labelling assay and lactate dehydrogenase release analysis; measured the activity of caspase‐1/‐3/‐8/‐9 and the release of interleukin‐1β; and determined the expression of apoptosis‐associated proteins and gasdermin D by apoptosis antibody array and Western blotting. Results: Enterococcus faecalis OG1RF reduced the mitochondrial membrane potential of the infected cells, increased the percentage of apoptotic and terminal deoxynucleotidyl transferase dUTP nick end labelling‐positive cells, and enhanced lactate dehydrogenase release. The expression of caspase‐3 and survivin and the activity of caspase‐3/‐8/‐9 were upregulated, while the expression of death receptor 6 was downregulated. The activity of caspase‐1/gasdermin D and the release of interleukin‐1β remained unaltered. Conclusion: Enterococcus faecalis OG1RF induced both intrinsic and extrinsic MG63 cell apoptosis via caspase‐3/‐8/‐9 activation but did not activate the pyroptotic pathway regulated by caspase‐1/gasdermin D.